Whole genome analysis of intestinal source Bacillus and its effect on the prevention and control of hybrid snakehead (Channa maculata ♀ × Channa argus ♂) nocardiosis - Zhou, Tingting; Cai, Ping; Li, Junwei; Li, Zhongsheng; Dan, Xueming; Huang, Xiande; Zhang, Xiaoyong (Frontiers in Marine Science, 2024)
In order to explore the antagonistic mechanism of Lysinibacillus sphaericus AEB18 against Nocardia seriolae, the whole genome of strain AEB18 was sequenced, and the effect of strain AEB18 in controlling nocardiosis of hybrid snakehead was verified in vitro and in vivo. Strain AEB18 genome was a circular DNA of 4,653,716 base pairs (bp) and GC content of 37.4%, predicting 4,529 coding genes, 108 tRNAs, 37 rRNAs, and 95 non-coding (nc)RNAs. The eggNOG (Non-supervised Orthologous Groups), GO (Gene Ontology), KEGG (Kyoto Encyclopedia of Genes and Genomes) and the CAZy (Carbohydrate-Associated Enzyme) database annotated the strain AEB18 genome to 3,965, 3,325, 2,061, and 112 genes, respectively. Furthermore, nine gene clusters, including polyketones, non-ribosomal synthetic peptides, β-lactones, terpenes, ribosomal synthetic peptides, and other secondary metabolites with bacteriostatic effect were obtained through the prediction of secondary metabolites of strain AEB18. After the addition of L. sphaericus AEB18 (1 × 10 9 CFU/g) with a mass fraction of 1% to the basal diet for 21 days, the weight gain rate and the activity of amylase in intestinal chyme of hybrid snakehead were significantly increased (P < 0.05). In addition, hybrid snakehead fed with L. sphaericus AEB18 supplemented diets showed significantly reduced mortality rate (P < 0.05) after N. seriolae infection, compared with the control group (mortality rate was 100%). Overall, L. sphaericus AEB18 positively affected hybrid snakeheads, promoted growth and reduced mortality rate of hybrid snakeheads with nocardiosis. Taken together, the L. sphaericus AEB18 possesses great potential as a biocontrol agent, which can be commercially developed to improve disease control in freshwater aquaculture.